Rural mothers' beliefs and practices about diagnosis, treatment, and management of children health problems: A qualitative study in marginalized Southern Pakistan - Farooq Ahmed; Farooq Ahmed; Najma Iqbal Malik; Sidra Zia; Abdul Samad Akbar; Xiaoyu Li; Muhammad Shahid; Muhammad Shahid; Muhammad Shahid; Kun Tang (Frontiers Media S.A., 2023)
IntroductionAppropriate health-seeking beliefs and practices are indispensable for the survival and development of children. In this study, we explore childcare beliefs and practices of rural mothers and analyze the different ways childhood illness is diagnosed and managed in a marginalized rural community in Southern Pakistan.MethodsUsing purposive sampling, in-depth interviews are conducted to obtain qualitative data from 20 illiterate and rural mothers in addition to 15 healthcare providers in the district Rajanpur of South Punjab.Results and discussionThe findings reveal that rural mothers' access to healthcare and therapeutic programs is impeded due to geographical isolation, structural inequalities, poverty, and illiteracy. Consequently, evil eyes, witchcraft, and spirits are recognized as potential threats to children's health and nutrition. Therefore, the treatment of childhood morbidity and malnutrition is mostly performed with folk, domestic, herbal, magico-religious remedies, and spiritual healing methods. The current study also highlights that many low-income and rural mothers tend to normalize childhood illness when they become unable to advocate for their children's health and nutrition. Besides improving low-income mothers' access to healthcare facilities, health education and risk communication at the field level through field health staff could be most effective for health promotion.